Transversal Competences: Their Importance and Learning Processes by Higher Education Students - Maria José Sá; Sandro Serpa (MDPI AG, 2018)
At a time when the labour market is blocked and simultaneously rapidly changing, with the emergence of new professional and scientific areas, the higher education mission becomes less indisputable and more indeterminate and challenging. This uncertainty was the leitmotiv for this essay, which aims to discuss the importance of attaining transversal competences in higher education. To achieve this goal, a bibliographical research was carried out on the attention that is currently given by higher education institutions to this topic, how they respond to the need for increasingly more transversal training and how they develop a curriculum that meets these requirements. Thus, in methodological terms, a thorough research on the literature addressing the topic of transversal competences was carried out; subsequently, a document search was conducted and a qualitative review and analysis of the documents collected was performed to justify our stance. Our analysis allowed concluding that the context of indeterminacy regarding the future has variations, considering the geographical and political situation, the social context and the activity sector. Furthermore, attitudes, expectations and predispositions are also critical elements for the success of this process of transversal competences’ attainment. This latter factor is central in this process, as there is often a gap between students’ expectations regarding the competences they expect to attain in higher education and the proposals that frame their training at the micro, meso and macrosocial levels and which take the need to attain transversal competences in higher education for granted.